2012
DOI: 10.1155/2012/718617
|View full text |Cite
|
Sign up to set email alerts
|

Dextran Sodium Sulphate Colitis Mouse Model: Traps and Tricks

Abstract: Inflammatory bowel disease (IBD) is a complex multifactorial disease of unknown etiology. Thus, dozens of different animal models of IBD have been developed in past decades. Animal models of IBD are valuable and indispensable tools that provide a wide range of options for investigating involvement of various factors into the pathogenesis of IBD and to evaluate different therapeutic options. However, the dextran sulphate sodium (DSS-) induced colitis model has some advantages when compared to other animal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
697
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 730 publications
(739 citation statements)
references
References 66 publications
34
697
0
8
Order By: Relevance
“…We observed no significant differences between WT and ZnR/ GPR39 KO mice in all parameters during all 6 days of DSS treatment, disease phase (figure 3d-f ). Previous studies indicated that clinical manifestations during the acute disease phase do not necessarily reflect the histological severity of the disease in the colon tissue [32], in agreement with our results. Because the clinical and histopathological scores were similar between the genotypes on the 6th day of DSS treatment, we continued to study whether ZnR/GPR39 affects a recovery phase, following removal of DSS.…”
Section: Resultssupporting
confidence: 92%
“…We observed no significant differences between WT and ZnR/ GPR39 KO mice in all parameters during all 6 days of DSS treatment, disease phase (figure 3d-f ). Previous studies indicated that clinical manifestations during the acute disease phase do not necessarily reflect the histological severity of the disease in the colon tissue [32], in agreement with our results. Because the clinical and histopathological scores were similar between the genotypes on the 6th day of DSS treatment, we continued to study whether ZnR/GPR39 affects a recovery phase, following removal of DSS.…”
Section: Resultssupporting
confidence: 92%
“…We therefore analyzed Akt signaling pathway in the mucosa of C57BL/6J mice treated with dextran sulfate sodium (DSS), a well-known colitis model of epithelial injury. 18 As reported previously by us, 19 a gradual decrease in cell proliferation, increased disease activity index (DAI) (Supplementary Figure 1A) and colon length shortening (Supplementary Figure 1B) were observed in DSS-treated mice. Moreover, Akt activation augments as revealed by the presence of the active form of Akt (phospho-Akt Thr308; pAkt308) ( Figure 1a).…”
Section: Resultssupporting
confidence: 75%
“…These studies have been conducted in one strain of chickens (Cobb). However, it has been determined that the IP of different strains is affected differently by DSS ingestion (Perše and Cerar, 2012). Lipopolysaccharide, found in the outer coat of gram-negative bacteria (Tran, 2009), has been well established as a model to increase IP in mice (Williams et al, 2013), rats (Ruan et al, 2014) and pigs .…”
Section: Introductionmentioning
confidence: 99%